LabBitcoin: FPGA IoT Testbed for Bitcoin Experiment with Energy Consumption - Hayashi, Victor T.; Almeida, Felipe V. de; Komo, Andrea E. (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg), 2021)
This paper describes a Field Programmable Gate Array (FPGA) testbed that enables Bitcoin experimentation in real-time with energy consumption. The Internet of Things (IoT) infrastructure enables practical activities considering a remote lab paradigm to allow students and enthusiasts to obtain a deep understanding of Blockchain technology, considering higher cognitive domains according to the Bloom taxonomy. The proposed solution is validated with an open-source Bitcoin miner implementation in Verilog, mobile, and web interfaces for energy consumption monitoring. This testbed may be used to foster Verilog design challenges for FPGA devices that provide a suitable solution considering performance and energy consumption metrics.